2014
DOI: 10.1016/j.jef.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of kimchi, a salt fermented vegetable, is not associated with hypertension prevalence

Abstract: a b s t r a c tBackground: The aim of this study was to investigate the association between hypertension and kimchi, a salt-fermented vegetable, intake. , and 2012. In the final analysis, a total of 20,114 Korean adults (men ¼ 7,815, women ¼ 12,299) was included. Daily energy, nutrient, and kimchi intake were assessed using 24-hour dietary recall. The odds ratios for hypertension, according to groups of quintiles of kimchi consumption by gender, were assessed using logistic regression and multivariable models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 27 publications
(23 reference statements)
2
14
0
Order By: Relevance
“…It was also discovered that we also have to pay attention to the impact of potassium on the diseases which were used as covariables in order to control the impact of sodium on diseases. Such results are consistent with other studies, which revealed that blood pressure rise is more influenced by sodium/ potassium intake ratio that considered potassium intake than absolute sodium intake and [19] which high consumption of kimchi, fermented food using salt, is irrelevant to prevalence rate of hypertension [10].…”
Section: Results Of Logit Analysis On Strokesupporting
confidence: 93%
See 1 more Smart Citation
“…It was also discovered that we also have to pay attention to the impact of potassium on the diseases which were used as covariables in order to control the impact of sodium on diseases. Such results are consistent with other studies, which revealed that blood pressure rise is more influenced by sodium/ potassium intake ratio that considered potassium intake than absolute sodium intake and [19] which high consumption of kimchi, fermented food using salt, is irrelevant to prevalence rate of hypertension [10].…”
Section: Results Of Logit Analysis On Strokesupporting
confidence: 93%
“…Also, through the study on the risk of stroke and intake of potassium, which is known to be involved in sodium excretion, Bazzano et al [9] drew a result that the risk of stroke increases with less potassium intake. In addition, in the result of their recent study on nutritional epidemiologic survey of kimchi, Korea's representative fermented food and prevalence rate of hypertension, Song and Lee [10] found that there is no correlation between high consumption of kimchi and the prevalence rate of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of sodium chloride generally in fermented products has been extensively studied due to the correlation with elevated blood pressure and increasing occurrence of cardiovascular diseases (Lee S. M. et al, 2012 ). In the case of kimchi, Song and Lee ( 2014 ) reported that its consumption could not be correlated to hypertension prevalence. The latter results from both sodium excess and potassium deficiency in the body; since vegetables are a major source of potassium, the high intake may neutralize the negative effects of sodium intake.…”
Section: Biological Changes During Kimchi Fermentationmentioning
confidence: 99%
“…The health promoting properties such as anticancer, antimicrobial activities are attributed to the residing natural microbes especially lactic acid bacteria (Anh, 2015). A detailed study on consumption of Kimchi, (famous Korean salt-fermented food and a good source of minerals, vitamins, fibers, and other trace nutrients) suggested that the intake of kimchi containing a large volume of salt was not associated with hypertension, indeed, high consumption of kimchi helps to neutralize the salt imbalance (Song & Lee, 2014).…”
Section: Impact Of Fpbs On Health Status Of Consumersmentioning
confidence: 99%